A Growth Pattern, and Caffeine Degradation of Acinetobacter gerneri KAFS 47 on Glucose Media with Addition of Caffeine - Arimurti, Sattya; Wicaksono, Bagus Aji; Siswanto, Siswanto (Journal of Coffee and Sustainability, 2024)
Caffeine-degrading bacteria are organisms capable of utilizing caffeine as a carbon and nitrogen source. Acinetobacter gerneri KAFS 47 is known to possess the ability to degrade caffeine. The type of carbon source present in the growth medium influences the growth pattern and the caffeine degradation capabilities of caffeine-degrading bacteria. The objective of this study was to ascertain the growth pattern of A. gerneri KAFS 47 and to analyze the pattern of caffeine degradation by A. gerneriKAFS 47 in growth media following the addition of caffeine during the logarithmic phase.  The research methodology encompasses the following steps: 1.) Constructing a growth curve for A. gerneri KAFS 47 using M9 supplemented with 2.5 g/L glucose, M9 supplemented with 2.5 g/L caffeine, M9 supplemented with 2.5 g/L glucose with an additional 2.5 g/L caffeine introduced midway through the logarithmic phase (12 hours), and M9 supplemented with 2.5 g/L glucose with an added 5 g/L caffeine at the midpoint of the logarithmic phase (12 hours); and  2.) developing a caffeine degradation curve for A. gerneri KAFS 47. The addition of caffeine during the logarithmic phase at concentrations of 2.5 g/L and 5 g/L enhanced the logarithmic growth phase of  A. gerneriKAFS 47 in media with a glucose carbon source. Notably, the degradation of caffeine by A. gerneri KAFS 47 was observed to be slower in media containing glucose with added caffeine (2.5 g/L and 5 g/L) compared to media where caffeine served as the sole carbon source.